Predictors of return to work after a year since stroke: A systematic review - Rinita Mascarenhas; Akshatha Nayak; Dhaval Pawani; Zulkifli Misri; Amreen Mahmood; K Vijaya Kumar; Vani Lakshmi R. Iyer (Clinical Epidemiology and Global Health, 2024)
Purpose: Recent studies have identified an increased prevalence of stroke in young patients. Therefore, we aimed to systematically review the predictors contributing to return to work (RTW) within 1 year after a stroke and summarize the identified gaps. Methods: Searches were conducted using keywords from the PubMed, Scopus, CINHAL, Embase, and Cochrane databases from inception to 2023. This review was based on the Preferred Reporting Items for Systematic Review and Meta-analysis for Scoping Reviews (PRISMA-ScR) guidelines. The retrieved articles were screened for titles and abstracts using the Rayyan QCR software. The quality of the study was determined using The Joanna Briggs Institute (JBI) critical appraisal tool. Results: Eight studies encompassing 4587 stroke participants were included in the review. Ischemic stroke, male sex, and ability to perform activities of daily living were positive predictors of RTW, whereas older age, severe stroke, poor consciousness, and impaired cognition were negative predictors. Coping skills and ethnicity were found to be non-significant. Conclusion: This review highlights predictors of RTW post-stroke. The Facilitation of RTW among stroke survivors necessitates a comprehensive rehabilitation program that emphasizes predictors such as stroke severity, functional independence, impaired cognition, and consciousness. In addition, vocational rehabilitation should be based on an individual's capacity, modifying the workplace environment, and prescribing assistive devices to enhance RTW. Systematic review registration: International Prospective Register of Systematic Reviews (PROSPERO) registration number CRD42022348983.